A Note on the Flow of Capital in Outstanding Common and Preferred Shares Between Canada and the United States - Robertson, Matthew (Journal of Financial and Quantitative Analysis, 1972)
Matthew Robertson, A Note on the Flow of Capital in Outstanding Common and Preferred Shares Between Canada and the United States, The Journal of Financial and Quantitative Analysis, Vol. 7, No. 1 (Jan., 1972), pp. 1425-1427